PENGARUH PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NATAFARI BANDAR LAMPUNG - Patmarina Hepiana; Ardansyah Ardansyah; Erisna Nuria; Sari Amelia Diah (SOSIALITA, 2022)
This research was conducted with the aim of knowing the effect of Job Training on the performance of employees of PT. Natafari Bandar Lampung, the effect of work discipline on employee performance at PT. Natafari Bandar Lampung, the effect of Job Training & Work Discipline on Employee Performance of PT. Natafari Bandar Lampung. This research uses research by quantitative research and association approach. The source of the data obtained is raw data using the method of collecting observation data, research documents and questionnaires. The population in the research are all employees of PT. Natafari Bandar Lampung a total of 45 people. The instrument requirements test used is a validity test and a reliability test. The data analysis method uses multiple linear regression, and the hypothesis testing refers to the t-test and...F-test. The results.....this research..shows that job training has an effect on employee performance. Natafari Bandar Lampung, job training has an effect on employee performance at PT. Natafari Bandar Lampung, job training and work discipline affect the performance of employees at PT. Natafari Bandar Lampung.